2009
DOI: 10.1097/mao.0b013e3181b4ec89
|View full text |Cite
|
Sign up to set email alerts
|

Vascular Findings in the Stria Vascularis of Patients With Unilateral or Bilateral Ménière's Disease

Abstract: The stria vascularis may be ischemic bilaterally both in bilateral and unilateral Ménière's disease. Abnormal findings in the contralateral ears in unilateral Ménière's disease reported in previous studies might be related to poor vascularity of the stria vascularis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
20
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
8
1
1

Relationship

2
8

Authors

Journals

citations
Cited by 31 publications
(21 citation statements)
references
References 23 publications
1
20
0
Order By: Relevance
“…Circulatory disturbances affecting both temporal bones have been proposed in more detailed studies of patients with unilateral MD. The abnormalities found in the stria vascularis of the asymptomatic ear were related to a significant reduction in the number of vessels, which was similar both in the symptomatic and asymptomatic or contralateral ear [Kariya et al, 2009].…”
Section: Discussionmentioning
confidence: 72%
“…Circulatory disturbances affecting both temporal bones have been proposed in more detailed studies of patients with unilateral MD. The abnormalities found in the stria vascularis of the asymptomatic ear were related to a significant reduction in the number of vessels, which was similar both in the symptomatic and asymptomatic or contralateral ear [Kariya et al, 2009].…”
Section: Discussionmentioning
confidence: 72%
“…Thus, regulation of fluid homeostasis by the SV is assumed to be highly dependent on circulating GCs. In Ménière's disease, the SV is known to be severely atrophic and shows degeneration (26). In such pathologic condition, fluid regulation in the SV by GCs is assumed to be disturbed, and the clinical efficacy of GCs for Ménière's disease may well be diminished.…”
Section: Discussionmentioning
confidence: 99%
“…Another recent cohort study showed that chronic inflammation and immune dysregulation, the characteristics of SLE, induce a high incidence of atherosclerotic vascular events and accelerated cardiovascular disease (21). The stria vascularis requires a high level of blood supply to maintain the endocochlear potential levels and that the impaired homeostasis of the cochlear blood supply due to arteriosclerosis results in degeneration of the stria vascularis (22, 23). A human temporal bone study by Nomiya et al showed that patients with arteriosclerosis had a decreased number of cochlear hair cells, as compared with normal controls (24).…”
Section: Discussionmentioning
confidence: 99%